Conventional and Islamic indices in Indonesia: A Comparison on Performance, Volatility, and the Determinants - Pranata, Nika; Nurzanah, Nurzanah (The Indonesian Capital Market Review, 2015)
The purpose of this study is to evaluate performance and volatility of Islamic andconventional stock indices along with their determinant factor variables in Indonesia. The study adopts: (1) Capital Asset Pricing Model (CAPM) to compare the performance of the Jakarta Islamic Index (JII) to represent Islamic indexandLQ45 to represent the conventional, (2) beta calculation to measure volatility, and (3) Autoregressive Distributed Lag (ARDL) to capture the determinants and the reason behind the outperformance. The data coverage is from January 2006 to November 2015. The study finds that: (1) There is no significant differenceon performance between JII and LQ45, (2) JII is less volatile than LQ45, except in 2010, and (3)JII performance is less affected by external factorsexcept for crude oil price. Moreover, the result implies challenge for the authorities to educate society, particularly whom concern to shari’ah principles, with information that Islamic index performance is not much difference from conventional index and less volatile.